Novel injectable gallium-based self-setting glass-alginate hydrogel composite for cardiovascular tissue engineering. (1st August 2019) - Clarkin, Owen M.; Wu, Bing; Cahill, Paul A.; Brougham, Dermot F.; Banerjee, Dipanjan; Brady, Sarah A.; Fox, Eoin K.; Lally, Caitríona
Graphical abstract: Highlights: Glass-alginate hydrogels are synthesized from Ga-based glass formulation. The setting hydrogel has high network connectivity, strength and stiffness. Its slow network setting rate is suitable for injectable gel application. The cell study shows great bio-compatibility of this composite. Abstract: Composite biomaterials offer a new approach for engineering novel, minimally-invasive scaffolds with properties that can be modified for a range of soft tissue applications. In this study, a new way of controlling the gelation of alginate hydrogels using Ga-based glass particles is presented. Through a comprehensive analysis, it was shown that the setting time, mechanical strength, stiffness and degradation properties of this composite can all be tailored for various applications. Specifically, the hydrogel generated through using a glass particle, wherein toxic aluminium is replaced with biocompatible gallium, exhibited enhanced properties. The material's stiffness matches that of soft tissues, while it displays a slow and tuneable gelation rate, making it a suitable candidate for minimally-invasive intra-vascular injection. In addition, it was also found that this composite can be tailored to deliver ions into the local cellular environment without affecting platelet adhesion or compromising viability of vascular cells in vitro.